2011
DOI: 10.4103/0256-4947.83219
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal use of risk reduction therapy in peripheral arterial disease patients at a major teaching hospital

Abstract: BACKGROUND AND OBJECTIVES:Current evidence suggests that modification of atherosclerosis risk factors plays an important role in reducing adverse cardiovascular outcomes in patients with peripheral arterial disease (PAD). This study was undertaken to determine whether patients in this high-risk group were adequately using risk factor modification therapy.DESIGN AND SETTING:Prospective study of consecutive patients with PAD from a teaching hospital.PATIENTS AND METHODS:The collected data included information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Between 74% (France) and 82% (multinational) of patients with PAD were prescribed antiplatelets. ASA prescription rates varied between 28% (the Netherlands) and 55% (Saudi Arabia) in this population. In Germany, 21% of patients with symptomatic PAD received clopidogrel, versus 43% for ASA .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Between 74% (France) and 82% (multinational) of patients with PAD were prescribed antiplatelets. ASA prescription rates varied between 28% (the Netherlands) and 55% (Saudi Arabia) in this population. In Germany, 21% of patients with symptomatic PAD received clopidogrel, versus 43% for ASA .…”
Section: Resultsmentioning
confidence: 92%
“…Current patterns of antiplatelet secondary prophylaxis in patients with CAD or PAD were found in many reports. In total, 14 large observational studies based on database and registry data were selected (Table 3) [35,[40][41][42][43][44][45][46][47][48][49][50][51][52]. These studies covered a spectrum of countries from North America (Canada), Europe (including France, Germany, Poland, and The Netherlands) and Asia-Pacific (China, Japan, Saudi Arabia, and New Zealand).…”
Section: Practice Patternsmentioning
confidence: 99%
“…There may be several factors contributing to suboptimal rates of best medical therapy, including lack of access to care, drug insurance coverage, or clinician time and education, among other factors. 36,37 There may be opportunities to improve rates of best medical therapy along with physical activity through patient education in the clinic, PAD awareness campaigns, and further integration of PAD education into medical school curricula. 38,39 Second, we found that preoperative factors were the most important predictors of 1-year MALE or death, while intraoperative features did not significantly improve model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are opportunities to improve PAD care by understanding patients’ perioperative risk and optimizing them before and after revascularization. There may be several factors contributing to suboptimal rates of best medical therapy, including lack of access to care, drug insurance coverage, or clinician time and education, among other factors . There may be opportunities to improve rates of best medical therapy along with physical activity through patient education in the clinic, PAD awareness campaigns, and further integration of PAD education into medical school curricula .…”
Section: Discussionmentioning
confidence: 99%
“…Despite demonstrated benefits, some studies have shown a lack of uptake of these medications in patient risk management. 7,20,21 A recent multi-center audit of BMT use in PAD patients post-ilioinguinal bypass demonstrated that 33.1% of patients were not discharged on BMT overall. 22 The authors reported that only 3.6% of patients were not discharged on any antithrombotic agent, either antiplatelet or anticoagulant.…”
Section: Introductionmentioning
confidence: 99%